Identification of Gender in Early Pregnancy Using Cell-Free Fetal Dna - Budi Junio Hermawan; Bobby Indra Utama; Andani Eka Putra (Andalas Obstetrics And Gynecology Journal, 2026)
Introduction: Traditionally, chorionic villus sampling and amniocentesis can be used to help identify fetal gender around 11 weeks of pregnancy. However, the risk of miscarriage with these procedures is approximately 1 to 3%. The discovery of cell-free fetal DNA (cffDNA) fragments in the plasma and serum of pregnant women carrying male fetuses has made reliable and accurate diagnosis using non-invasive procedures an option for determining fetal gender. To determine the success rate of fetal gender identification in early pregnancy using Cell Free Fetal DNA. Methods: An analytical observational research method to identify fetal gender in early pregnancy through Cell Free Fetal DNA examination in maternal blood. A total of 70 samples were collected using quota sampling technique. Data analysis was performed using sensitivity and specificity tests, as well as cross-sectional analysis to determine the relationship between PCR test results and gender at birth.      Results: The PCR test has low sensitivity (14.29%), meaning the test is less effective in correctly detecting male gender, resulting in many false negatives. However, it has high specificity (98.11%), indicating its excellent ability to detect female gender with very few false positives. Additionally, the Pearson Chi-Square statistical test resulted in a p-value of 0.033 (p < 0.05), indicating a statistically significant relationship between PCR test results and gender at birth.   Conclusion: Statistically, this test is better at identifying females than males, with a lower error rate for females.